Using remote Sensing technique to detect the environmental changes inHalabjah north Eastern Iraq - Ahmad, Walid (Iraqi Journal of Science, 2024)
This study aims to detect the changes that happen in Halabjah area and special inDarbandikhan Lake. As well as the vegetation cover during 1990 to 2000. Theimage data used in this study are Landsat 5TM (30-4-1990) and Landsat 7 ETM+(28-6-2000) and it has been compared and inter- printed visually.two kinds oftechniques have been used in this study; image differencing and normalizeddifference vegetation index (NDVI). Ground truth checking was done to detect thechanges that take place in the study area. The results gained from this study shows that the volume of the water has beenreduced for about (1558005800) cubic meter and the area of vegetation coverreduced for about (39399.4) Hectare. This indicates great changes took place in thestudy area. These changes are due to reduction of rain fall and the policy of waterbalance